Hamlet, prince of Denmark - Sellen, Derek; Shakespeare, William, 1564-1616.; Visintin, Fabio (Genoa [Italy] : Black Cat, 2003)
An adaptation of William Shakespeare play in which a Danish prince seeks vengeance for his father's murder after being visited by his ghost. Includes background information, activities, and a CD.
"Beginner"--Cover.
Enhanced compact disc.
Young Adult
System requirements stated.
Keywords: Readers (Elementary).; Readers; CD-ROMs.; Compact discs; Reading materials; CD-ROMs.; Compact discs